LAÇOS FAMILIARES E INTEGRAÇÃO COMUNITÁRIA DOS PRESOS NA PENITENCIÁRIA INDUSTRIAL DE GUARAPUAVA: UMA PROPOSTA DE PLANO DE AÇÃO - RATTES, MARINALDO JOSÉ (2023)
The submission of prisoners in penal institutions in the state of Paraná to the Central de Vagas do Sistema Penal – CV/DEPEN created by Joint Resolution 003/2012, caused family and community distancing, with negative effects on resocialization. In this sense, it is based on the practical assumption that the Vacancy Center departed from the Penal Execution Law by inserting that the fulfillment of the sentence will be in the prison with a vacancy, without ensuring the conviviality of the convicts with their families and social environment, to which they belonged before imprisonment. It is worth noting that the Penal Execution Law, by expressing the extension of constitutional rights to prisoners, seeks to avoid discriminatory treatment and safeguard humanity and dignity in the execution of the sentence, as well as guarantee that the convict serves his sentence in a place close to his family in conditions of social reintegration. Thus, the gap between the Vacancy Center and the Criminal Execution Law motivated this technical report, which aims to propose strategic actions aimed at promoting, maintaining and strengthening family ties and community integration of prisoners at the Guarapuava Industrial Penitentiary (PIG), centered on the human dignity of the inmate. The research was centered on a qualitative approach, developed through the case study method with a descriptive character. Primary data were collected from a focus group interview, composed of six convicts; and individual interviews based on a semi-structured script with two employees of the prison system. In order to understand and interpret the speeches from the focus group and individual interviews, the content analysis technique was used based on five categories of analysis: a) the right to humane and dignified treatment in the execution of the sentence; b) the right to family life; c) the right to social assistance; d) the right to visitation on certain days, communication and contact with the outside world; and, e) the right to stay in a place close to their social and family environment. To elaborate the action plan, the SWOT technique and the 5W2H tool were applied to the analysis categories. In the SWOT analysis, facts and situations related to the categories of analysis were considered, the external and internal environments were examined, resulting in the identification of opportunities (O), threats (T), strengths (S) and weaknesses (W), and the indication of conceptually distinct strategies, tactics and alternative actions. Once the SWOT analysis was completed, the 5W2H tool was used to develop the action plan, which consists of the following actions: I) Review the guidelines used for custody and transfer of the convict, in order to enable him to be guarded and remain in a prison facility closer to his social and family; II) Improve social assistance; III) Adapt the physical structure; IV) Increase the capacity of visitors per weekend in a fair number to the convicts; V) Facilitate the obtaining of the visit credential (card); VI) Facilitate the scheduling and carrying out of virtual visits; VII) Promote access to correspondence; VIII) Adopt measures to prevent the practice of humiliating searches; IX) Provide a sufficient number of jobs for convicts; X) Expand educational assistance (offering school instruction and professional training). These actions have the purpose of promoting improvements in the governance of the PIG, in particular, establishing dynamics that can ensure conditions for the effective family and social reintegration of the convict, as well as safeguarding humanity and dignity in the execution of the sentence.